Functional nickel complexes of N-heterocyclic carbene ligands in pre-organized and supported thin film materials - Wang, Xinjiao; Sobota, Marek; Kohler, Florian; Morain, Bruno; Melcher, Berthold Ulrich; Laurin, Mathias; Wasserscheid, Peter; Libuda, Jörg; Meyer, Karsten (Journal of Materials Chemistry, 2012)
Nickel(ii) complexes with double alkyl chain functionalized N-heterocyclic carbene (NHC) ligands, [NiCl (C MIM) ] and [NiCl (C C IM) ], where C MIM = 1-dodecyl-3-methylimidazolin-2-ylidene (1) and C C IM = 1,3-didodecylimidazolin-2-ylidene (2), have been prepared and fully characterized by H NMR, C NMR, and CHN elemental analyses. Furthermore, we have developed a system, in which double long alkyl chain derivatized Ni-NHC complexes are dissolved in the related ionic liquid crystalline 1,3-didodecylimidazolium tetrafluoroborate, [C C IM][BF ], to form pre-organized structures for enhanced reactivity. Remarkably, differential scanning calorimetry, polarized optical microscopy, and temperature-programmed IR reflection absorption spectroscopy performed on a mixture of 10 wt% Ni complexes in [C C IM][BF ] demonstrate that this system retains an ionic liquid crystalline phase; even after immobilization onto a silica-100 support with pore filling α = 1. © 2012 The Royal Society of Chemistry.

Surface-functionalized ionic liquid crystal-supported ionic liquid phase materials: Ionic liquid crystals in mesopores - Kohler, Florian; Morain, Bruno; Weiß, Alexander; Laurin, Mathias; Libuda, Jörg; Wagner, Valentin; Melcher, Berthold Ulrich; Wang, Xinjiao; Meyer, Karsten; Wasserscheid, Peter (ChemPhysChem, 2011)
The influence of confinement on the ionic liquid crystal (ILC) [C C Im][OTf] is studied using differential scanning calorimetry (DSC), polarized optical microscopy (POM), and diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS). The ILC studied is supported on Si-based powders and glasses with pore sizes ranging from 11 to 50 nm. The temperature of the solid-to-liquid-crystalline phase transition seems mostly unaffected by the confinement, whereas the temperature of the liquid-crystalline-to-liquid phase transition is depressed for smaller pore sizes. A contact layer with a thickness in the order of 2 nm is identified. The contact layer exhibits a phase transition at a temperature 30 K lower than the solid-to-liquid-crystalline phase transition observed for the neat ILC. For applications within the "supported ionic liquid phase (SILP)" concept, the experiments show that in pores of diameter 50 nm a pore filling of α>0.4 is sufficient to reproduce the phase transitions of the neat ILC. © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.